Fibrous Reinforced Concrete Slabs (University of Khartoum Engineering Journal, 2022)
The paper presents the results of a theoretical and an experimental work performed at the KhartoumUniversity, Civil Engineering Department Structure lab. The work aimed to obtain knowledge concerning theinfluence of steel fibers on the behaviour of reinforced concrete slabs. A comparative study was conductedtheoretically and experimentally. In the experimental work, tests were conducted on six simply supported slabs,which were divided into three groups according to steel fiber contents 0%, 1%, and 2% by volumes, each groupcontained two slabs, one isotropically reinforced and the other orthotropically reinforced. All slabs were subjectedto uniformly distributed load. The deflections were measured using displacement transducers, which werepositioned at different locations on the bottom surface of concrete slab. The strains were also measured usingstrain gages embedded on reinforcement surface at different locations and glued on the top and bottom concretesurface. The failure modes were observed and the load was recorded using load cell. The instruments wereconnected to TDS303 Data Logger. The performance of the specimens is analyzed and compared with thetheoretical investigations using BS 8110 Codes and yield line method based upon calculations of the moment ofresistance and load carrying capacity respectively. The deflection, curvature and strain were calculated based onthe elastic theory through the area moment theorems and partially cracked section. It was found that the steel fibercontent had an influence ranging from little to significant on the tested behaviours of slabs. Good correlation oftheoretical and experimental results was clearly noticed when compared to each other.